Results of Multilevel Containment Measures to Better Protect Lung Cancer Patients From COVID-19: The IEO Model - de Marinis, Filippo; Attili, Ilaria; Morganti, Stefania; Stati, Valeria; Spitaleri, Gianluca; Gianoncelli, Letizia; Del Signore, Ester; Catania, Chiara; Rampinelli, Cristiano; Omodeo Salè, Emanuela; Spaggiari, Lorenzo; Mastrilli, Fabrizio; et al. (Frontiers in Oncology, 2020)
A novel coronavirus causing severe acute respiratory syndrome (SARS), named SARS-CoV-2, has been identified at the end of 2019. The spread of coronavirus disease 2019 (COVID-19) has progressively expanded from China involving several countries throughout the world, leading to the classification of the disease as a pandemic by the World Health Organization (WHO). According to published reports, COVID-19 severity and mortality are higher in elderly patients and in those with active comorbidities. In particular, lung cancer patients were reported to be at high risk of pulmonary complications related to SARS-CoV2 infection. Therefore, the management of cancer care during the COVID-19 pandemic is a crucial issue, to which national and international oncology organizations replied with recommendations concerning patients receiving anticancer treatments, delaying follow-up visits and limiting caregiver admission to the hospitals. In this historical moment, medical oncologists are required to consider the possibility to delay active treatment administration, based on case-by-case risk/benefit evaluation. Potential risks associated with COVID-19 infection should be considered, considering tumor histology and natural course, disease setting, clinical conditions and disease burden, together with the expected benefit, toxicities (e.g. myelosuppression or interstitial lung disease) and response obtained from the planned or ongoing treatment. In this study, we report the results of proactive measures including social media, telemedicine and telephone triage for screening patients with lung cancer during the COVID-19 outbreak in the European Institute of Oncology (Milan, Italy). Proactive management and containment measures, applied in a structured and daily way, significantly guaranteed to individuate in advance patients with suspected symptoms related to COVID-19, limiting their admission to our cancer center, thus being able to protect other patients from possible contamination and at the same time guarantee to the suspected patients the immediate treatment and evaluation in referral centers for COVID-19.